A polyester heat shrinkable film

By increasing the amount of monomer residues in copolyester resin A that destroys PET crystallization and mixing it with polyester resin B, the problem of difficult to use recycled materials for amorphous copolyester heat shrink film is solved, and the goal of high shrinkage and crystallinity is achieved, supporting environmental protection and circular economy is achieved.

CN115895202BActive Publication Date: 2025-04-01WUXI CHONGHUA NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211290692.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-21
Publication Date
2025-04-01
Estimated Expiration
2042-10-21

AI Technical Summary

Technical Problem

The existing non-crystalline copolyester heat shrink films are difficult to use large amounts of polyester bottles recovered by physical methods, and cannot be recycled again, which violates the requirements of environmental protection and circular economy.

Method used

By increasing the amount of monomer residues in copolyester resin A that destroys PET crystallization to more than 30%, and mixing with polyester resin B, the properties of the film in terms of heat shrinkage and crystallinity are ensured.

Benefits of technology

It achieves high shrinkage and crystallinity, solves the adhesion problem, and supports the large amount of recycled materials, which meets the requirements of environmental protection and circular economy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure DEST_PATH_IMAGE001
    Figure DEST_PATH_IMAGE001
Patent Text Reader

Abstract

The invention discloses a polyester heat shrinkable film, comprising a copolyester resin A containing a diol component and a dicarboxylic acid component, and a polyester resin B containing a diol component and a dicarboxylic acid component; the copolyester resin A, the crystallization temperature Tc measured by differential scanning calorimetry (DSC) at a cooling rate of 10°C / min cannot be detected; the polyester resin B, the crystallization temperature Tc measured by differential scanning calorimetry (DSC) at a cooling rate of 10°C / min can be measured; the prepared shrinkable film, after being placed in a 90°C water bath for 10 seconds, has a shrinkage rate in the main shrinkage direction greater than or equal to 65%; the prepared shrinkable film, the crystallization temperature Tc measured by differential scanning calorimetry (DSC) at a cooling rate of 10°C / min can be measured. In the present invention, the amount of monomer residues that destroy PET crystallization in the copolyester resin A is increased to more than 30% of the molar amount of the diol component in the copolyester resin A, and after being mixed with the polyester resin B, both the shrinkage and the shrinkage rate can be guaranteed, and the crystallization and non-adhesion can be guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polyester shrinkable films, in particular to a polyester heat shrinkable film. Background Art

[0002] Polyester heat shrinkable film is a widely used shrink sleeve label material. This technology usually uses non-crystalline copolyester resin to extrude a thick sheet through an extruder, and then obtains a film with unidirectional or bidirectional orientation of the polymer chain through one or both of longitudinal stretching and transverse stretching.

[0003] A typical feature of this heat shrinkable film is that the oriented film prepared by the above steps can shrink as much as possible to the state before stretching and orientation when heated to between 50 degrees Celsius and 100 degrees Celsius to obtain a larger shrinkage rate. Therefore, this technology usually requires the use of non-crystalline copolyester to ensure that no crystallization occurs during the stretching and orientation of the thick sheet. Because crystallization usually "freezes" the movement of the molecular chain, hindering its ability to shrink at 50 degrees Celsius to 100 degrees Celsius, and reducing its heat shrinkage rate.

[0004] Another typical feature of heat shrinkable film is that the oriented film prepared by the above steps has good leveling when applied to the surface of the film using one or more conventional organic solvents in the industry, such as 1,4-dioxane, 1,3-dioxane, and tetrahydrofuran. It can dissolve or swell the surface layer of the film, so that when the dissolved or swollen surface layer is attached to another surface layer, they can be bonded together and maintain a certain bonding strength after the solvent evaporates. The industry uses this method to prepare shrink film into shrink sleeve labels. This necessary step is called "hand-to-hand", and the organic solvent used is called "hand-to-hand solvent". Generally speaking, non-crystalline polyester film is easily dissolved or swelled by hand-to-hand solvent, and the bonding strength of hand-to-hand can meet the application requirements. However, if the crystallinity of the film increases, the hand-to-hand solvent will find it difficult to dissolve or swell the film, resulting in a decrease in hand-to-hand fastness, affecting subsequent use.

[0005] In short, it is a common practice in the industry to prepare polyester heat shrinkable film using non-crystalline copolyester. Here, "non-crystalline copolyester (PETg)" usually refers to the use of diol monomers with steric hindrances such as branches and rings, hereinafter referred to as "steric hindrance monomers", including but not limited to neopentyl glycol (NPG), cyclohexanedimethanol (CHDM), 2-methyl-1,3-propanediol (MPDO), isosorbide (ISB), 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD), etc., to copolymerize and modify polyethylene terephthalate (PET), destroying the crystallinity of PET. When using differential scanning calorimetry (DSC) at a temperature change rate of 10 oC / min to measure its cold crystallization temperature Tcc and hot crystallization temperature Tmc, they cannot be detected or the crystallization enthalpy is less than or equal to 1J / g. Several copolyesters for shrink films are widely used in the market, such as Embrace TM LV from Eastman Company of the United States, Skygreen TM S2012, SF700 from SK Company of South Korea, HSF from Jiangsu Guanghui Packaging Co., Ltd., WS-501 from Jiangyin Huahong, etc., which are all such products.

[0006] Although the above-mentioned non-crystalline copolyester heat shrinkable film, hereinafter referred to as non-crystalline film, has many advantages in application, its disadvantages and shortcomings are also obvious. First, it is difficult to mix this type of shrinkage film with polyester bottle flakes recycled by physical method. The polyester bottle flakes recycled by physical method here refer to the recycled polyester bottle flakes obtained after consumers use the polyester bottle and then recycled by the recycling system through physical methods such as crushing, washing, and drying, hereinafter referred to as physical method rPET. In particular, when the content of polyester bottle flakes or polyester bottle flakes recycled by physical method in the shrinkage film formula exceeds 25%, the heat shrinkage rate of the shrinkage film will decrease, and the hand-closing fastness will decrease, thereby affecting the use of the heat shrinkage film. This performance decline is essentially due to the fact that polyester bottle flakes or polyester bottle flakes recycled by physical method are crystalline polymers. The mixing of such substances into the shrinkage film will increase the crystallinity of the film, thereby reducing the shrinkage performance and hand-closing performance.

[0007] Second, this type of shrink film is difficult to recycle using physical methods. Because the non-crystalline film has no crystals and a low softening point, when it undergoes the aforementioned physical recycling process, crushing, cleaning, and drying, it gradually softens, causing the recycled bottle flakes to stick to each other and agglomerate, resulting in the entire recycling system not being able to operate normally. Of course, if a large amount of crystalline polyester bottle flakes or recycled bottle flakes are mixed, it is beneficial to improve the adhesion and agglomeration, but as mentioned in the first disadvantage above, mixing crystalline polymers will lead to a decrease in the shrinkage performance and hand-jointing performance of the shrink film, so it is difficult to achieve a balance in practical applications.

[0008] As countries around the world pursue environmental protection and circular economy, more and more food and beverage brands are paying more and more attention to packaging materials containing recycled materials and being recyclable. Many countries have also developed roadmaps requiring packaging materials to contain 30% or more recycled materials. In the polyester field, the so-called "recycled materials" usually refer to recycled bottle flakes supported by a complete recycling system, and these recycled materials are all crystalline polyesters. For a long time, the widely used non-crystalline copolyester heat shrink film has been considered difficult to add 30% of physical recycled materials and can no longer be physically recycled. This is inconsistent with the current circular environmental protection model advocated by the plastic packaging industry, which uses more recycled materials and recyclable packaging.

[0009] In order to solve the problem that non-crystalline membranes cannot use recycled materials in large quantities and cannot be recycled, the industry usually uses chemical methods for recycling and reuse. The chemical recycled materials here are hereinafter referred to as chemical rPET. Chemical rPETg refers to the method of collecting used polyester waste, depolymerizing it under high temperature conditions by chemical methods to obtain small molecular monomers or oligomers, and then purifying these monomers, and using these purified monomers to repolymerize them into polyester or copolyester under high temperature conditions. Although this chemical recycling method has achieved a certain degree of recycling cycle, it adds two high-energy-consuming depolymerization and repolymerization steps, which is obviously contrary to the concept of low carbon and environmental protection.

[0010] Patent No. “CN110662638B” discloses “a polyester film” and Patent No. “CN114729113A” discloses “a crystallizable reactor-grade polyester composition”, but the polyester films in these two patents do not contain polyester resin B. Summary of the invention

[0011] The object of the present invention is to provide a polyester heat shrinkable film.

[0012] The innovation of the present invention is that the amount of monomer residues that destroy PET crystallization in the copolyester resin A is increased to more than 30% of the molar amount of the diol component in the copolyester resin A, and after being mixed with the polyester resin B, both the shrinkage and the shrinkage rate can be guaranteed, and crystallization and non-adhesion can be guaranteed.

[0013] In order to achieve the above-mentioned object of the invention, the technical solution of the present invention is:

[0014] A polyester heat shrinkable film comprises a copolyester resin A containing a diol component and a dicarboxylic acid component, and a polyester resin B containing a diol component and a dicarboxylic acid component;

[0015] For copolyester resin A, the crystallization temperature Tc measured by differential scanning calorimetry (DSC) at a cooling rate of 10 °C / min was undetectable;

[0016] For polyester resin B, the crystallization temperature Tc measured by differential scanning calorimetry (DSC) at a cooling rate of 10 °C / min is between 130 °C and 30 °C;

[0017] The shrinkage rate of the prepared shrink film in the main shrinkage direction after being placed in a 90°C water bath for 10 seconds is greater than or equal to 65%;

[0018] The prepared shrink film can be measured by differential scanning calorimetry (DSC) at a cooling rate of 10°C / min.

[0019] Furthermore, the molar content of monomer residues capable of destroying the crystallinity of PET in the prepared shrink film is greater than or equal to 20%.

[0020] Furthermore, the dicarboxylic acid component in the copolyester resin A includes at least one of terephthalic acid, phthalic acid, and isophthalic acid.

[0021] Furthermore, the diol component in the polyester resin B includes ethylene glycol, and the dicarboxylic acid component in the polyester resin B includes terephthalic acid and isophthalic acid; the polyester resin B is crystalline PET bottle flakes, crystalline PET recycled bottle flakes, PET polyester, recycled PET polyester or recycled PET bottle flakes.

[0022] Furthermore, the amount of ethylene glycol residues in the copolyester resin A is 0-70% of the molar amount of the diol component in the copolyester resin A, the amount of diethylene glycol residues in the copolyester resin A is 0-20% of the molar amount of the diol component in the copolyester resin A, and the amount of monomer residues in the copolyester resin A that can destroy PET crystallization is 30-100% of the molar amount of the diol component in the copolyester resin A.

[0023] Furthermore, the glass transition temperature Tg of the copolyester resin A is greater than or equal to 65°C and less than or equal to 82°C.

[0024] Furthermore, the prepared shrink film is a single-layer or multi-layer thick sheet extruded from an extruder, which is prepared by stretching 4 to 5.5 times in the main shrinking direction.

[0025] Furthermore, the monomers capable of destroying PET crystallization include neopentyl glycol, cyclohexanedimethanol and 2-methyl 1,3-propylene glycol; the content of neopentyl glycol is 0-100 mol% of the diol content in the copolyester resin A, the content of cyclohexanedimethanol is 0-50 mol% of the total diol content in the copolyester resin A, and the content of 2-methyl 1,3-propylene glycol is 0-30 mol% of the total diol content in the copolyester resin A.

[0026] Furthermore, the shrink film is prepared by physical blending, melt extrusion, uniaxial or biaxial stretching.

[0027] Further, at least one layer contains a blend of copolyester resin A and polyester resin B.

[0028] The beneficial effects of the present invention are:

[0029] 1. The amount of monomer residues that destroy PET crystallization in copolyester resin A is increased to more than 30% of the molar amount of the diol component in copolyester resin A. After mixing with polyester resin B, it can ensure both shrinkage and shrinkage rate, as well as crystallization and non-adhesion.

[0030] 2. In the present invention, there is a certain phase separation after the copolyester resin A and the polyester resin B are mixed. During the directional stretching process, the copolyester resin A is oriented, and its shrinkage ability is maintained due to a certain phase separation with the polyester resin B. At the same time, the polyester resin B also maintains its crystallinity, which greatly improves the adhesion problem with the PET bottle flakes during the recycling process.

[0031] 3. After the copolyester resin A and the polyester resin B are mixed, there is a certain phase separation in the present invention. However, a certain amount of the copolyester resin A is frozen by the crystallization of the polyester resin B during the stretching process, which reduces the number of effective polymer chains that can shrink, and thus the shrinkage rate is insufficient. When the amount of monomer residues that destroy PET crystals in A is less than 30%, when the polyester resin B is mixed, the shrinkage rate of the film is clearly shown in Comparative Examples 1, 2, and 3 to be less than 65%. When the amount of monomer residues that destroy PET crystals in the copolyester resin A is greater than or equal to 30%, the ability of the monomer residues that destroy PET crystals to penetrate into the crystalline polyester phase during the film stretching and orientation process becomes stronger, and even when a large amount of polyester resin B is mixed, a shrinkage rate greater than 65% can be guaranteed. At the same time, the high content of polyester resin B also makes the mixed film show a strong tendency to crystallize, which is conducive to solving the adhesion problem.

[0032] 4. In the present invention, the content of neopentyl glycol is 0-100 mol% of the diol content in the copolyester resin A, and it can be kept in a non-crystalline state. When the content of cyclohexanedimethanol is greater than 50 mol% of the total diol content in the copolyester resin A, it shows stronger and stronger crystallinity. In the DSC test, the crystallization peak Tc is obvious; in addition, Tg gradually rises to about 95°C, which is not conducive to maintaining the shrinkage window of the shrink film in the temperature range of 60-90°C. When the content of 2-methyl 1,3-propanediol is greater than 30 mol% of the total diol content in the copolyester resin A, Tg drops below 62 degrees, and the shrinkage temperature range window will be too low, increasing the risk of shrinkage at normal ambient temperature. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention will be described clearly and completely below.

[0034] The copolyester resin A used in this patent is synthesized by conventional methods in the industry, and the polyester resin B is purchased from the market.

[0035] Preparation of film samples: Add the mixed resin mixture into a twin-screw extruder with a vacuum dehydration system to extrude a thick sheet of about 200 microns. Cut the thick sheet into thin sheets of about 12 cm*12 cm, put it into a biaxially stretched test machine, and stretch it about 1.1 times in one direction and 4 to 5.5 times in the other direction according to the requirements of the specific embodiment of this article at a temperature 5-25 degrees higher than the Tg temperature. The thickness of the film after stretching is about 40 microns.

[0036] The molar content of diol residues and dicarboxylic acid residues of copolyester resin A, polyester resin B and shrink film was determined by the Avance-600MHz (NMR) method of the Swiss Bruker nuclear magnetic resonance instrument, where the total molar content of diol was 100%, which was equal to the total molar content of diacid. The crystallization temperature Tc and the glass transition temperature Tg were tested by differential scanning calorimeter with reference to ASTMD3418. Unless otherwise specified, the heating and cooling rates are 10 ℃ / min. The shrinkage rate of the film after stretching was determined by cutting a 100mm*100mm square sample, placing it in a 90-degree water bath, keeping it for 10 seconds, and determining it according to the following formula without any restrictions on shrinkage:

[0037] Shrinkage rate%=[(100mm-length after shrinkage) / 100mm]*100%

[0038] Embodiment 1: A polyester heat shrinkable film comprises a copolyester resin A comprising a diol component and a dicarboxylic acid component, and a polyester resin B comprising a diol component and a dicarboxylic acid component; the copolyester resin A has an undetectable crystallization temperature Tc measured by differential scanning calorimetry (DSC) with reference to the measurement method of ASTM D 3418 at a cooling rate of 10°C / min; the dicarboxylic acid component in the copolyester resin A comprises terephthalic acid.

[0039] The amount of monomer residues capable of destroying PET crystallization in copolyester resin A is 100% of the molar amount of the diol component in copolyester resin A. The monomer capable of destroying PET crystallization includes neopentyl glycol, and the content of neopentyl glycol is 100 mol% of the diol content in copolyester resin A.

[0040] The glass transition temperature Tg of the copolyester resin A is 72°C.

[0041] The polyester resin B has a crystallization temperature Tc of 162°C measured by differential scanning calorimetry (DSC) with reference to the measurement method of ASTM D 3418 at a cooling rate of 10°C / min; the diol component in the polyester resin B includes ethylene glycol, and the dicarboxylic acid component in the polyester resin B includes terephthalic acid and isophthalic acid; the polyester resin B is a crystalline PET bottle flake.

[0042] The shrinkage rate of the prepared shrink film in the main shrinkage direction after being placed in a 90°C water bath for 10 seconds was 65%;

[0043] The prepared shrink film has a crystallization temperature Tc of 159°C as measured by differential scanning calorimetry (DSC) at a cooling rate of 10°C / min; the molar content of monomer residues capable of destroying the crystallinity of PET in the prepared shrink film is 20%.

[0044] The prepared shrink film is a single-layer or multi-layer thick sheet extruded from an extruder and stretched 4 times. The shrink film is prepared by physical blending, melt extrusion, uniaxial or biaxial stretching, and at least one layer contains a blend of copolyester resin A and polyester resin B.

[0045] Embodiment 2: A polyester heat shrinkable film comprises a copolyester resin A comprising a diol component and a dicarboxylic acid component, and a polyester resin B comprising a diol component and a dicarboxylic acid component; the copolyester resin A has an undetectable crystallization temperature Tc measured by differential scanning calorimetry (DSC) with reference to the measurement method of ASTM D 3418 at a cooling rate of 10°C / min; the dicarboxylic acid component in the copolyester resin A comprises terephthalic acid.

[0046] The amount of ethylene glycol residues in the copolyester resin A is 25% of the molar amount of the diol component in the copolyester resin A, the amount of diethylene glycol residues in the copolyester resin A is 10% of the molar amount of the diol component in the copolyester resin A, and the amount of monomer residues in the copolyester resin A that can destroy PET crystallization is 65% of the molar amount of the diol component in the copolyester resin A. The monomers that can destroy PET crystallization include neopentyl glycol, cyclohexanedimethanol and 2-methyl 1,3-propanediol; the content of neopentyl glycol is 20 mol% of the diol content in the copolyester resin A, the content of cyclohexanedimethanol is 25 mol% of the total diol content in the copolyester resin A, and the content of 2-methyl 1,3-propanediol is 20 mol% of the total diol content in the copolyester resin A.

[0047] The glass transition temperature Tg of copolyester resin A is 67°C.

[0048] The polyester resin B has a crystallization temperature Tc of 163°C measured by differential scanning calorimetry (DSC) with reference to the measurement method of ASTM D 3418 at a cooling rate of 10°C / min; the diol component in the polyester resin B includes ethylene glycol, and the dicarboxylic acid component in the polyester resin B includes terephthalic acid and isophthalic acid; the polyester resin B is crystalline PET recycled bottle flakes.

[0049] The shrinkage rate of the prepared shrink film in the main shrinkage direction after being placed in a 90°C water bath for 10 seconds was 75%;

[0050] The prepared shrink film has a crystallization temperature Tc of 163°C as measured by differential scanning calorimetry (DSC) at a cooling rate of 10°C / min; the molar content of monomer residues capable of destroying the crystallinity of PET in the prepared shrink film is 29%.

[0051] The prepared shrink film is prepared by stretching a single-layer or multi-layer thick sheet extruded from an extruder by 4.5 times.

[0052] Embodiment 3: A polyester heat shrinkable film comprises a copolyester resin A comprising a diol component and a dicarboxylic acid component, and a polyester resin B comprising a diol component and a dicarboxylic acid component; the copolyester resin A has an undetectable crystallization temperature Tc measured by differential scanning calorimetry (DSC) with reference to the measurement method of ASTM D 3418 at a cooling rate of 10°C / min; the dicarboxylic acid component in the copolyester resin A comprises isophthalic acid.

[0053] The amount of ethylene glycol residues in copolyester resin A is 70% of the molar amount of the diol component in copolyester resin A, and the amount of monomer residues in copolyester resin A that can destroy PET crystallization is 30% of the molar amount of the diol component in copolyester resin A. Monomers that can destroy PET crystallization include cyclohexanedimethanol and 2-methyl 1,3-propanediol; the content of cyclohexanedimethanol is 15 mol% of the total amount of diols in copolyester resin A, and the content of 2-methyl 1,3-propanediol is 15 mol% of the total amount of diols in copolyester resin A.

[0054] The glass transition temperature Tg of the copolyester resin A is 65°C.

[0055] The polyester resin B has a crystallization temperature Tc of 163°C measured by differential scanning calorimetry (DSC) with reference to the measurement method of ASTM D 3418 at a cooling rate of 10°C / min; the diol component in the polyester resin B includes ethylene glycol, and the dicarboxylic acid component in the polyester resin B includes terephthalic acid and isophthalic acid; the polyester resin B is crystalline PET recycled bottle flakes.

[0056] The shrinkage rate of the prepared shrink film in the main shrinkage direction after being placed in a 90° C. water bath for 10 seconds was 67%.

[0057] The prepared shrink film has a crystallization temperature Tc of 163°C as measured by differential scanning calorimetry (DSC) at a cooling rate of 10°C / min; the molar content of monomer residues capable of destroying the crystallinity of PET in the prepared shrink film is 20%.

[0058] The prepared shrink film is prepared by extruding a single-layer or multi-layer thick sheet from an extruder and stretching it 5 times.

[0059] Embodiment 4: A polyester heat shrinkable film comprises a copolyester resin A comprising a diol component and a dicarboxylic acid component, and a polyester resin B comprising a diol component and a dicarboxylic acid component; the copolyester resin A has an undetectable crystallization temperature Tc measured by differential scanning calorimetry (DSC) with reference to the measurement method of ASTM D 3418 at a cooling rate of 10°C / min; the dicarboxylic acid component in the copolyester resin A comprises terephthalic acid and phthalic acid.

[0060] The amount of diethylene glycol residues in copolyester resin A is 20% of the molar amount of the diol component in copolyester resin A, and the amount of monomer residues in copolyester resin A that can destroy PET crystallization is 80% of the molar amount of the diol component in copolyester resin A. Monomers that can destroy PET crystallization include cyclohexanedimethanol and 2-methyl 1,3-propanediol; the content of cyclohexanedimethanol is 50 mol% of the total amount of diols in copolyester resin A, and the content of 2-methyl 1,3-propanediol is 30 mol% of the total amount of diols in copolyester resin A.

[0061] The glass transition temperature Tg of the copolyester resin A is 70°C.

[0062] The polyester resin B has a crystallization temperature Tc of 201°C measured by differential scanning calorimetry (DSC) with reference to the measurement method of ASTM D 3418 at a cooling rate of 10°C / min; the diol component in the polyester resin B includes ethylene glycol, and the dicarboxylic acid component in the polyester resin B includes terephthalic acid; the polyester resin B is PET polyester.

[0063] The shrinkage rate of the prepared shrink film in the main shrinkage direction after being placed in a 90° C. water bath for 10 seconds was 70%.

[0064] The prepared shrink film has a crystallization temperature Tc of 199°C as measured by differential scanning calorimetry (DSC) at a cooling rate of 10°C / min; the molar content of monomer residues capable of destroying the crystallinity of PET in the prepared shrink film is 24%.

[0065] The prepared shrink film is prepared by stretching a single-layer or multi-layer thick sheet extruded from an extruder by 5.5 times.

[0066] Embodiment 5: A polyester heat shrinkable film comprises a copolyester resin A comprising a diol component and a dicarboxylic acid component, and a polyester resin B comprising a diol component and a dicarboxylic acid component; the copolyester resin A has an undetectable crystallization temperature Tc measured by differential scanning calorimetry (DSC) with reference to the measurement method of ASTM D 3418 at a cooling rate of 10°C / min; the dicarboxylic acid component in the copolyester resin A comprises terephthalic acid.

[0067] The amount of ethylene glycol residues in copolyester resin A is 10% of the molar amount of the diol component in copolyester resin A, the amount of diethylene glycol residues in copolyester resin A is 20% of the molar amount of the diol component in copolyester resin A, and the amount of monomer residues capable of destroying PET crystallization in copolyester resin A is 70% of the molar amount of the diol component in copolyester resin A. The monomer capable of destroying PET crystallization includes neopentyl glycol; the content of neopentyl glycol is 70 mol% of the diol content in copolyester resin A.

[0068] The glass transition temperature Tg of the copolyester resin A is 71°C.

[0069] The polyester resin B has a crystallization temperature Tc of 200°C measured by differential scanning calorimetry (DSC) at a cooling rate of 10°C / min with reference to the measurement method of ASTM D 3418; the diol component in the polyester resin B includes ethylene glycol, and the dicarboxylic acid component in the polyester resin B includes terephthalic acid; the polyester resin B is recycled PET polyester.

[0070] The shrinkage rate of the prepared shrink film in the main shrinkage direction after being placed in a 90° C. water bath for 10 seconds was 76%.

[0071] The prepared shrink film has a crystallization temperature Tc of 195°C as measured by differential scanning calorimetry (DSC) at a cooling rate of 10°C / min; the molar content of monomer residues capable of destroying the crystallinity of PET in the prepared shrink film is 35%.

[0072] The prepared shrink film is prepared by extruding a single-layer or multi-layer thick sheet from an extruder and stretching it 5 times.

[0073] Embodiment 6: A polyester heat shrinkable film comprises a copolyester resin A comprising a diol component and a dicarboxylic acid component, and a polyester resin B comprising a diol component and a dicarboxylic acid component; the copolyester resin A has an undetectable crystallization temperature Tc measured by differential scanning calorimetry (DSC) with reference to the measurement method of ASTM D 3418 at a cooling rate of 10°C / min; the dicarboxylic acid component in the copolyester resin A comprises terephthalic acid.

[0074] The amount of ethylene glycol residues in copolyester resin A is 25% of the molar amount of the diol component in copolyester resin A, the amount of diethylene glycol residues in copolyester resin A is 15% of the molar amount of the diol component in copolyester resin A, and the amount of monomer residues capable of destroying PET crystallization in copolyester resin A is 60% of the molar amount of the diol component in copolyester resin A. The monomer capable of destroying PET crystallization includes neopentyl glycol; the content of neopentyl glycol is 60 mol% of the diol content in copolyester resin A.

[0075] The glass transition temperature Tg of the copolyester resin A is 71°C.

[0076] The polyester resin B has a crystallization temperature Tc of 163°C measured by differential scanning calorimetry (DSC) with reference to the measurement method of ASTM D 3418 at a cooling rate of 10°C / min; the diol component in the polyester resin B includes ethylene glycol, and the dicarboxylic acid component in the polyester resin B includes terephthalic acid; the polyester resin B is recycled PET bottle flakes.

[0077] The amount of ethylene glycol residues in the polyester resin B is 98% of the molar amount of the diol component in the polyester resin B.

[0078] The shrinkage rate of the prepared shrink film in the main shrinkage direction after being placed in a 90° C. water bath for 10 seconds was 77%.

[0079] The prepared shrink film has a crystallization temperature Tc of 161°C as measured by differential scanning calorimetry (DSC) at a cooling rate of 10°C / min; the molar content of monomer residues capable of destroying the crystallinity of PET in the prepared shrink film is 29%.

[0080] The prepared shrink film is prepared by extruding a single-layer or multi-layer thick sheet from an extruder and stretching it 5 times.

[0081] Embodiment 7: A polyester heat shrinkable film comprises a copolyester resin A comprising a diol component and a dicarboxylic acid component, and a polyester resin B comprising a diol component and a dicarboxylic acid component; the copolyester resin A has an undetectable crystallization temperature Tc measured by differential scanning calorimetry (DSC) with reference to the measurement method of ASTM D 3418 at a cooling rate of 10°C / min; the dicarboxylic acid component in the copolyester resin A comprises terephthalic acid and phthalic acid.

[0082] The amount of monomer residues capable of destroying PET crystallization in copolyester resin A is 100% of the molar amount of the diol component in copolyester resin A. The monomers capable of destroying PET crystallization include neopentyl glycol and cyclohexanedimethanol; the content of neopentyl glycol is 75 mol% of the diol content in copolyester resin A, and the content of cyclohexanedimethanol is 25% of the diol content in copolyester A.

[0083] The glass transition temperature Tg of the copolyester resin A is 82°C.

[0084] The polyester resin B has a crystallization temperature Tc of 163°C measured by differential scanning calorimetry (DSC) with reference to the measurement method of ASTM D 3418 at a cooling rate of 10°C / min; the diol component in the polyester resin B includes ethylene glycol, and the dicarboxylic acid component in the polyester resin B includes terephthalic acid; the polyester resin B is recycled PET bottle flakes.

[0085] The amount of ethylene glycol residues in the polyester resin B is 98% of the molar amount of the diol component in the polyester resin B.

[0086] The shrinkage rate of the prepared shrink film in the main shrinkage direction after being placed in a 90° C. water bath for 10 seconds was 70%.

[0087] The prepared shrink film has a crystallization temperature Tc of 161°C as measured by differential scanning calorimetry (DSC) at a cooling rate of 10°C / min; the molar content of monomer residues capable of destroying the crystallinity of PET in the prepared shrink film is 38%.

[0088] The prepared shrink film is prepared by extruding a single-layer or multi-layer thick sheet from an extruder and stretching it 5 times.

[0089] Comparative Example 1: The copolyester resin A in Example 1 is adjusted so that the amount of ethylene glycol residues in the copolyester resin A is 72% of the molar amount of the diol component in the copolyester resin A, and the amount of monomer residues capable of destroying PET crystallization in the copolyester resin A is 28% of the molar amount of the diol component in the copolyester resin A. The monomer capable of destroying PET crystallization includes neopentyl glycol, and the content of neopentyl glycol is 28 mol% of the diol content in the copolyester resin A.

[0090] Comparative Example 2: The copolyester resin A in Example 2 is adjusted so that the amount of ethylene glycol residues in the copolyester resin A is 68% of the molar amount of the diol component in the copolyester resin A, the amount of diethylene glycol residues in the copolyester resin A is 10% of the molar amount of the diol component in the copolyester resin A, and the amount of monomer residues in the copolyester resin A that can destroy PET crystallization is 22% of the molar amount of the diol component in the copolyester resin A. The monomer that destroys PET crystallization includes cyclohexanedimethanol; the content of cyclohexanedimethanol is 22 mol% of the total amount of diols in the copolyester resin A.

[0091] Comparative Example 3: The copolyester resin A in Example 3 is adjusted so that the amount of ethylene glycol residues in the copolyester resin A is 68% of the molar amount of the diol component in the copolyester resin A, the amount of diethylene glycol residues in the copolyester resin A is 10% of the molar amount of the diol component in the copolyester resin A, and the amount of monomer residues in the copolyester resin A that can destroy PET crystallization is 22% of the molar amount of the diol component in the copolyester resin A. The monomer that destroys PET crystallization includes cyclohexanedimethanol; the content of cyclohexanedimethanol is 22 mol% of the total amount of diols in the copolyester resin A.

[0092] Comparative Example 4: In Comparative Example 1, polyester resin B is not added.

[0093]

[0094] The described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A polyester heat shrinkable film, characterized in that: A copolyester resin A comprising a diol component and a dicarboxylic acid component, and a polyester resin B comprising a diol component and a dicarboxylic acid component; For copolyester resin A, the crystallization temperature Tc measured by differential scanning calorimetry at a cooling rate of 10°C / min was undetectable; Polyester resin B, the crystallization temperature Tc measured by differential scanning calorimetry at a cooling rate of 10°C / min can be measured; The shrinkage rate of the prepared shrink film in the main shrinkage direction after being placed in a 90°C water bath for 10 seconds is greater than or equal to 65%; The prepared shrink film can be measured by the crystallization temperature Tc determined by differential scanning calorimetry at a cooling rate of 10°C / min; The dicarboxylic acid component in the copolyester resin A includes at least one of terephthalic acid, phthalic acid, and isophthalic acid; The amount of ethylene glycol residues in the copolyester resin A is 0-70% of the molar amount of the diol component in the copolyester resin A, the amount of diethylene glycol residues in the copolyester resin A is 0-20% of the molar amount of the diol component in the copolyester resin A, and the amount of monomer residues in the copolyester resin A that can destroy the crystallinity of PET is 30-100% of the molar amount of the diol component in the copolyester resin A; The monomers capable of destroying the crystallinity of PET include neopentyl glycol, cyclohexanedimethanol and 2-methyl 1,3-propylene glycol; the content of neopentyl glycol is 60-100 mol% of the diol content in the copolyester resin A, the content of cyclohexanedimethanol is 0-50 mol% of the total diol content in the copolyester resin A, and the content of 2-methyl 1,3-propylene glycol is 0-30 mol% of the total diol content in the copolyester resin A; The polyester resin B is PET polyester; The molar content of monomer residues capable of destroying the crystallinity of PET in the prepared shrink film is greater than or equal to 20%.

2. A polyester heat shrinkable film, characterized in that: A copolyester resin A comprising a diol component and a dicarboxylic acid component, and a polyester resin B comprising a diol component and a dicarboxylic acid component; For copolyester resin A, the crystallization temperature Tc measured by differential scanning calorimetry at a cooling rate of 10°C / min was undetectable; Polyester resin B, the crystallization temperature Tc measured by differential scanning calorimetry at a cooling rate of 10°C / min can be measured; The shrinkage rate of the prepared shrink film in the main shrinkage direction after being placed in a 90°C water bath for 10 seconds is greater than or equal to 65%; The prepared shrink film can be measured by the crystallization temperature Tc determined by differential scanning calorimetry at a cooling rate of 10°C / min; The dicarboxylic acid component in the copolyester resin A includes at least one of terephthalic acid, phthalic acid, and isophthalic acid; The amount of ethylene glycol residues in the copolyester resin A is 0-70% of the molar amount of the diol component in the copolyester resin A, the amount of diethylene glycol residues in the copolyester resin A is 0-20% of the molar amount of the diol component in the copolyester resin A, and the amount of monomer residues in the copolyester resin A that can destroy the crystallinity of PET is 60-100% of the molar amount of the diol component in the copolyester resin A; The monomers capable of destroying the crystallinity of PET include neopentyl glycol, cyclohexanedimethanol and 2-methyl 1,3-propylene glycol; the content of neopentyl glycol is 0-100 mol% of the diol content in the copolyester resin A, the content of cyclohexanedimethanol is 0-50 mol% of the total diol content in the copolyester resin A, and the content of 2-methyl 1,3-propylene glycol is 0-30 mol% of the total diol content in the copolyester resin A; The polyester resin B is PET polyester; The molar content of monomer residues capable of destroying the crystallinity of PET in the prepared shrink film is greater than or equal to 20%.

3. The polyester heat shrinkable film according to claim 1 or 2, characterized in that: The diol component in the polyester resin B includes ethylene glycol, and the dicarboxylic acid component in the polyester resin B includes terephthalic acid and isophthalic acid.

4. The polyester heat shrinkable film according to claim 1 or 2, characterized in that: The polyester resin B is a crystalline PET bottle flake.

5. The polyester heat shrinkable film according to claim 1 or 2, characterized in that: The polyester resin B is recycled PET polyester.

6. The polyester heat shrinkable film according to claim 1 or 2, characterized in that: The polyester resin B is recycled PET bottle flakes.

7. The polyester heat shrinkable film according to claim 1 or 2, characterized in that: The glass transition temperature Tg of the copolyester resin A is greater than or equal to 65°C and less than or equal to 82°C.

8. The polyester heat shrinkable film according to claim 1 or 2, characterized in that: The prepared shrink film is a single-layer or multi-layer thick sheet extruded from an extruder and is prepared by stretching 4 to 5.5 times in the main shrinking direction.

9. The polyester heat shrinkable film according to claim 1 or 2, characterized in that: The shrink film is prepared by physical blending, melt extrusion, and uniaxial or biaxial stretching.

10. The polyester heat shrinkable film according to claim 8, characterized in that: At least one layer contains a blend of copolyester resin A and polyester resin B.

Citation Information

Patent Citations

  • Methods for recycling polyester films and polyester containers thereof

    CN110662638B

  • Catalyst system for crystallizable reactor grade resins

    CN114729113A

  • Polyester shrink label having improved low-temperature heat shrinkability

    JP1987095341A